Hubungan Hipertensi dengan Pembesaran Jantung pada Pasien di Ruang Perawatan - Suradi Efendi; Nour Sriyanah; Nirawati Nirawati; Djunaedi Djunaedi (PT.Mantaya Idea Batara, 2022)
Hypertension is an increase in the pulse rate so that the systolic blood pressure is 130 mmHg or more and the diastolic pressure is 80 or more or more mmHg. The enlargement of the heart or cardiomegaly that occurs in hypertension is originally a process of physiological adaptation, but with the continued addition of cardiomegaly it will become a pathological process. Ghiffary AM (2019) research explained that 89% of the samples had cardiomegaly hypertension. And another study conducted by Muhtri (2018) found that out of 60 hypertensive patients, the Cardiothoracic Ratio (CTR) value of all patients was more than 50%, indicating that hypertensive patients tended to improve. The purpose of this study was to determine the relationship between hypertension and heart disease in patients treated in the Asoka treatment room of RSUD dr. La Palaloi Hospital, Maros Regency. This type of research is descriptive analytics with a cross-sectional research approach, where a sample of 154 people took data samples using total sampling with observation sheet instruments in the medical record room of Dr La Palaloi Hospital, Maros Regency. The results showed that there was a relationship between hypertension and heart disease in patients treated in the Asoka treatment room, dr. La Palaloi Hospital, Maros Regency (p = 0.003). Suggestions from this study are expected to dr La Palaloi Hospital, Maros Regency, to further intensify the provision of blood pressure information, especially the incidence of hypertension and cardiomegaly to all patients and the progress of management.